Search, Price Dispersion, and Local Competition: Estimating Heterogeneous Search Costs in Retail Gasoline Markets - Mitsukuni Nishida; Marc Remer (U.S. Department of Justice, Antitrust Division, Economic Analysis Group (EAG), 2014)
Information frictions play a key role in a wide array of economic environments and are frequently incorporated into formal models as search costs. Yet, as search costs are typically unobserved, little empirical work investigates the determinants of the distribution of consumer search costs and the implications for policy. This paper explores the sources of heterogeneity in consumer search costs and how this heterogeneity and market structure shape firms' equilibrium pricing and consumers' search behavior in retail gasoline markets. We estimate the distribution of consumer search costs using price data for a large number of geographically isolated markets across the United States. The results demonstrate that the distribution of consumer search costs varies significantly across geographic markets and that market and population characteristics, such as household income, explain some of the variation. Policy counterfactuals suggest that the shape of the consumer search cost distribution has important implications for both government policy and firms' strategic pricing behavior. The experiments reveal that (1) the search cost distribution needs to be sufficiently heterogeneous to generate equilibrium price dispersion, and (2) the market-level expected price paid decreases in the number of firms, but consumers with high search costs may be worse off from an increased number of firms.
Keywords: 330